Lymph node tuberculosis with genital involvement: Case report: Tuberculosis ganglionar con compromiso genital: Reporte de caso - Atencio Paulino, Joel Isaac (2024)
We present the case of a 44-year-old male patient with a family history of lymphoma and hyperthyroidism. He started the disease three months before admission to hospital with pain in the right leg, abdominal pain, weight loss and night sweats. He was diagnosed in his hospitalization with ascites in a cavity of undetermined etiology, and multiple polygastric and fossa lymph nodes right iliac. At 6 months, the symptoms persist and a nodule is added on the penis, left testicular edema and purulent discharge from the right inguinal node, being diagnosed orchiepididymitis. Initially he had negative markers for tuberculosis (TB), however, a lymph node biopsy was performed and the analysis with Xpert MTB/RIF where it resulted positive. The patient improved considerably with anti-TB treatment and antibiotics for purulent discharge.